Implementation Of Principal's Transformational Leadership in Improving Teacher Performance Motivation at SMA Negeri 11 Palembang City - Hasinah Hasinah; Alhadi Yan Putra; Suherman Suherman (International Journal of Educational Evaluation and Policy Analysis, 2025)
This study aims to find out the Implementation of Transformational Leadership of School Principals in Improving Teacher Motivation and Performance at SMA Negeri 11 Palembang City. The research was conducted at SMA Negeri 11 Palembang City in November 2024, the research method used is descriptive qualitative research, namely by conducting interviews and observations on research objects for teachers and education staff. The results of the study stated that the transformational leadership applied succeeded in increasing the motivation and performance of teachers and education staff at SMA Negeri 11 Palembang.